Financial Intermediation In The Pre-Consolidated Banking Sector In Nigeria - Hesse, Heiko (The World Bank, 2007)
This paper uses unique bank-by-bank balance sheet and income statement information to investigate the intermediation efficiency in the Nigerian pre-consolidated banking sector during 2000-05. The author analyzes whether the Central Bank of Nigeria's policy of recent banking consolidation can be justified and rationalized by looking at the determinants of spreads. A spread decomposition and panel estimations show that the reform of the banking sector could be the first step to raise the intermediation efficiency of the Nigerian banking sector. The author finds that larger banks have enjoyed lower overhead costs, increased concentration in the banking sector has not been detrimental to the spreads, both increased holdings of liquidity and capital might have led to lower spreads in 2005, and a stable macroeconomic environment is conducive to a more efficient channeling of savings to productive investments